2019
DOI: 10.1371/journal.pone.0210891
|View full text |Cite
|
Sign up to set email alerts
|

Tailored NEOadjuvant epirubicin, cyclophosphamide and Nanoparticle Albumin-Bound paclitaxel for breast cancer: The phase II NEONAB trial—Clinical outcomes and molecular determinants of response

Abstract: Background This study evaluated the feasibility of achieving high response rates in stage II or III breast cancer by tailoring neoadjuvant therapy using clinical and histopathological features and the Oncotype DX Breast Recurrence Score. Genomic determinants of response and resistance were also explored. Patients and outcome measures Fifty-one patients were enrolled. The primary cohort comprised 40 patients: 15 human epidermal growth factor receptor type 2 (HER2)-amplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…On the contrary, usage of EC before Nab-Pac resulted in 50% of treated patients with BC having neutropenia at the end of treatment, with 18% of them having grade 3 or higher neutropenia. 8 These data suggest that the sequence Nab-Pac plus EC might be better for combination with immunotherapy than the opposite one. However, the stronger effects recorded at surgery might also be explained by long-term consequences of Nab-Pac and/or the sum of the two treatments and not only by an intrinsic stronger immune-depleting effect of EC.…”
Section: Discussionmentioning
confidence: 96%
“…On the contrary, usage of EC before Nab-Pac resulted in 50% of treated patients with BC having neutropenia at the end of treatment, with 18% of them having grade 3 or higher neutropenia. 8 These data suggest that the sequence Nab-Pac plus EC might be better for combination with immunotherapy than the opposite one. However, the stronger effects recorded at surgery might also be explained by long-term consequences of Nab-Pac and/or the sum of the two treatments and not only by an intrinsic stronger immune-depleting effect of EC.…”
Section: Discussionmentioning
confidence: 96%
“…Recent clinical trials have shown that concomitant or sequential administration of the most effective cytotoxic compounds (namely anthracyclines, taxanes, cyclophosphamide and, in some contexts, platinum compounds) in the neoadjuvant treatment setting yields the best clinical results in terms of pCR and reduction of the risk of disease relapses. 25 , 31 35 Some of these studies compared neoadjuvant anthracycline-taxane regimens of different duration, and showed that longer ChT duration is associated with a higher percentage of pCR rates. However ChT schedules that were compared in these studies also contained different cytotoxic agents and different combination regimens, thus making it unclear if treatment duration is actually responsible for the observed differences in terms of clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases this disease has become fatal because of its multifactorial origin and also because it has a great number of exogenous and endogenous factors that can stimulate different pathways [3]. In early BrC, gene expression profiles are determined for hormone receptor (HR)-positive disease and human epidermal growth factor type 2 receptor (HER2) status which define if a patient is likely to receive systemic therapy and are therefore used to guide their treatment [4]. Approximately 60-70% of primary BrC cases express positive estrogen receptors (ER+) or positive progesterone receptors (PR+) or both and are hormone responsive.…”
Section: Breast Cancer (Brc)mentioning
confidence: 99%
“…However, about 15-20% of BrC cases are in the category of triple-negative phenotype owing to their lack of ER, PR, and amplified HER2. Commonly, ER+ hormone-dependent BrCs have a better prognosis and are often responsive to antihormone therapy [4].…”
Section: Breast Cancer (Brc)mentioning
confidence: 99%